Analysis of alcohol in cosmetic products by headspace gas chromatography – mass spectrometry - Hashim, Puziah; Che Man, Yaakob; Kassim, Norrahimah (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
The Muslim consumers are very concerned of the presence of alcohol, in particular the presence of ethanol in cosmetic products. Nowadays, there are many cosmetic products in the market being labelled and claimed to be alcohol-free. In this study, our aim is to analyse the alcohol content in cosmetic products claimed to be alcohol-free using the headspace gas chromatography-mass spectrometry (GC/MS) method. The linear concentration range is 1-1000ppm and the correlation coefficient is relatively good (R2=0.99270.) The method is very sensitive as the detection limit (LOD) and the limits of quantification (LOQ) of the ethanol are approximately 7ppb and 34ppb, respectively. Eleven samples of cosmetic product were analysed and the concentration range were 7ppb-600ppm.